Numerical Modal Analysis of Reinforced Concrete Slab with Opening - Risan, Hussam K.; Farhan, Omar Shamal; Abbas, Hiba Imad (Al-Nahrain Journal for Engineering Sciences, 2017)
Openings in reinforced concrete (RC) slabs are usually created as a result of variations in construction function, architectural or mechanical necessities. Heavy equipment loads resulting from mechanical system of any building are often carried by RC slabs. Even the static analysis and design of RC slabs with opening is not clearly stated in the available international Codes, dynamic analytical solution for such structure is complex._x000D_ In this paper, numerical analysis based on finite element approach is utilized to implement the modal analysis of RC slabs. Opening size and position was parametrically studied. Slab natural frequency or periods in addition to, the mode shape were registered. The results showed that the opening size and position involved in RC slab had a significant change in the value of natural frequency and period for the high level modes. The material nonlinearity affect on free vibration analysis of RC opening slab with different levels of stiffness modifiers was taken into account. The dynamic characteristics of RC opening slab as a function of stiffness modifier degree was numerically measured for six mode shapes. The paper found that a reduction in stiffness modifier value greatly reduce the .natural frequency of RC opening slab.